(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
Kidney organoids represent a transformative leap in regenerative medicine, disease modeling, and pharmacological testing, providing sophisticated three-dimensional (3D) in vitro replicas that faithfully recapitulate the architecture and functionality of the human excretory system. Originating from human pluripotent stem cells (hPSCs), including induced pluripotent stem cells (iPSCs) and embryonic stem cells (ESCs), these organoids emulate essential renal components such as nephrons, collecting ducts, vascular networks, and interstitial stroma. This enables detailed investigations into embryonic kidney development, pathophysiological mechanisms underlying disorders like chronic kidney disease (CKD), polycystic kidney disease (PKD), and acute kidney injury (AKI), as well as high-throughput screening for therapeutic compounds. This comprehensive review synthesizes cutting-edge advancements from 2024 to 2025, emphasizing breakthroughs in organoid maturation through hypoxic conditioning, extracellular matrix (ECM) engineering, vascular integration, and biofabrication techniques like 3D bioprinting. Innovations such as branched organoids, organoids-on-a-chip, and assembloids have enhanced structural fidelity, functional plumbing for waste excretion, and modeling of complex diseases including APOL1-mediated CKD. By incorporating hypoxic gradients (5-10% O2) to mimic fetal environments, researchers have promoted endothelial cell proliferation and nephron interconnectivity, while ECM manipulations using decellularized scaffolds and supramolecular hydrogels have facilitated glomerular basement membrane formation and tubular elongation. Co-culture strategies with ureteric bud progenitors and immune cells have advanced excretory system integration, addressing previous limitations in collecting duct formation. Applications extend to personalized medicine via patient-derived iPSCs, genetic editing with CRISPR/Cas9 for mutation correction, and in vivo transplantation models demonstrating neo-vascularization and urine production. Challenges persist, including organoid immaturity, scalability for clinical use, and immunogenicity, but interdisciplinary approaches combining bioinformatics, single-cell RNA sequencing (scRNA-seq), and organ-on-chip platforms are paving the way for bioengineered kidneys. This article, enriched with schematic diagrams, confocal microscopic images, transmission electron microscopy (TEM) visuals, and comparative tables, highlights the pivotal role of kidney organoids in accelerating bench-to-bedside translations, potentially alleviating the global burden of ESRD through regenerative therapies.